Análisis de las estrategias digitales en Instagram que influyen en la decisión de compra de los consumidores menores de 30 años que solicitan comida por delivery en Lima Metropolitana - Antezana Febres, Julia Patricia (2021)
The general objective of this research is to determine how digital strategies on Instagram influence the purchase decision of consumers under 30 years of age who request food for delivery in Metropolitan Lima. The type of research is applied and mixed and have a quantitative approach. In this research, a virtual survey was applied to 391 people under the age of 30 who use the social network Instagram and request the food delivery service. The first chapter describes the problem of how digital strategies in the social network Instagram can influence in the decision of consumers who request food delivery service. In addition, the sample calculation. In the second chapter, presents the objectives and hypotheses of the investigation and, which are related to the problem to be solved and the details of the elaboration of research instrument. The third chapter presents the investigation background and the theoretical bases applied. The fourth chapter shows the results of the investigation with the corresponding graphs and the relationship validation of the study variables through Spearman's analysis, which obtained a positive relation. The chapter number five presents study conclusions, which support that digital strategies are relevant when the consumer decides to request food by delivery, due to the fact that they can be influenced during the purchase decision process. The sixth chapter shows some recommendations for delivery’s food companies, with the purpose that they can maximize their services.